THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT WATER RESOURCES DEPARTMENT, COPYRIGHT WORKS AND SPATIAL PLAN OF NORTH SUMATRA PROVINCE - Herlina - Dalimunthe (Movere Journal, 2022)
This study entitled "The Influence of Work Motivation, Work Discipline on Employee Performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province". The purpose of this study was to determine whether there is an influence of work motivation, Work Discipline on Employee Performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province”. The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 59 employees at the Department of Water Resources, Cipta Karya and Spatial Planning, North Sumatra Province, using a saturated sample of 59 respondents. The method used in this research is descriptive quantitative method. The data analysis technique used multiple linear regression analysis with the regression equation Y = 5.838 + 205X1 + 354X2 + e. Partial test results (t) were obtained for 2.614 for work motivation and 4.606 for work discipline. Meanwhile, the results of the simultaneous F test were obtained at 49,025. And the results obtained in this study showed an R2 value of 63.6%, so it can be concluded that work motivation and work discipline have a positive and significant effect on employee performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province and the remaining 36, 4% is influenced by other factors.